2002
DOI: 10.1128/jb.184.13.3682-3688.2002
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Regiospecificity in Biphenyl Dioxygenase by Active-Site Engineering

Abstract: Structure 6:571-586, 1998), we developed a three-dimensional model of KF707 BphA1 of Pseudomonas pseudoalcaligenes KF707. Based on structural information about the amino acids which coordinate the catalytic nonheme iron center, we constructed 12 site-directed BphA1 mutants with changes at positions 227, 332, 335, 376, 377, and 383 and expressed these enzymes in Escherichia coli. The Ile335Phe, Thr376Asn, and Phe377Leu Bph Dox mutants exhibited altered regiospecificities for various PCBs compared with wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
48
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 42 publications
11
48
0
3
Order By: Relevance
“…Supportive evidence provided by this work and a previous study (12) shows that residue 335 and especially residue 336 are directly implicated in enzyme turnover rates and regiospecificity. Replacing Phe 336 by Met or Ile as in p4 (Ala 335 -Met 336 ) or p8 (Ala 335 -Ile 336 ) variants resulted in a change in regiospecificity toward 2,2Ј-CB.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Supportive evidence provided by this work and a previous study (12) shows that residue 335 and especially residue 336 are directly implicated in enzyme turnover rates and regiospecificity. Replacing Phe 336 by Met or Ile as in p4 (Ala 335 -Met 336 ) or p8 (Ala 335 -Ile 336 ) variants resulted in a change in regiospecificity toward 2,2Ј-CB.…”
Section: Discussionsupporting
confidence: 59%
“…KF707 BPDO and B-356 BPDO catalyze the oxygenation of a much narrower range of PCB congeners than LB400 BPDO. Nevertheless, replacement of region III of LB400 BphA by that of KF707 or of B356 created enzymes that oxygenated a much broader range of PCB congeners (6,8,9,12). This shows that region III amino acids are not the only ones influencing the catalytic activity toward chlorobiphenyl, but it also shows that the sequence pattern of region III of LB400 BphA is not optimal for catalytic activity toward chlorobiphenyls.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[11c, 12] Concerning BPDO, residues Ile335 and Thr376 were determined to alter the substrate scope and regioselectivity for the dihydroxylation of biphenyl. [13] Previous studies using Pseudomonas pseudoalcaligenes KF707 BPDO, demonstrated that Ile335 was very important for determining substrate specificity and regioselectivity. The substrate scope for a range of polychlorinated biphenyls (PCB) was strongly associated with the amino acid side chain in this position.…”
Section: Mutant's Selection and Designmentioning
confidence: 99%
“…All enzymes with broad substrate specificity contain asparagine at the 376 position, whereas the enzymes with narrow substrate specificity contain threonine at this site. [15] Different mutations have been performed on this residue of BPDO. The introduction of amino acids smaller than Thr resulted in enzyme variants with reduced activity, while the inclusion of larger amino acids precluded substrate binding.…”
Section: Mutant's Selection and Designmentioning
confidence: 99%